HOW ARE MSMES PROMOTED BY MILLENNIALS? VISUAL ANALYSIS OF THE GENPI WEBSITE - M. Agung DHARMAJAYA, Agus SUROSO, RefiusPradipta SETYANTO, M. Elfan KAUKAB (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper explores destination online promotions carried out by millennials related to MSMEs in these destinations. It critically examines the photos and texts describing the destinations published on the GenerasiPesona Indonesia (GenPI/a community consisting of netizens who have interest in tourism) website using keywords that reflect the industry of small and medium enterprises. Despite GenPI’s high productivity and strong orientation in promoting local MSMEs, there are shortcomings and limitations in the less facilitative promotions such as unprofessional photoshoot and the loss of human interest component. Therefore, the need to train GenPI volunteers in designing advertisements and their promotional texts arises. This paper contributes to tourism studies, highlighting how the millennials market tourism destinations among themselves by using user-generated content. It also offers some ways to promote a destination, especially a new one, by employing the right framing to develop the local economy. These ways should encourage user-generated content carried out in a systematically programmed site as GenPI to line with the sustainable tourism paradigm. These, in turn, will benefit the local economy.